Catheter ablation for atrial fibrillation in patients with end‐stage heart failure and eligibility for heart transplantation. (13th December 2020) - Sohns, Christian; Marrouche, Nassir F.; Costard‐Jäckle, Angelika; Sossalla, Samuel; Bergau, Leonard; Schramm, Rene; Fuchs, Uwe; Omran, Hazem; Rubarth, Kerstin; Dumitrescu, Daniel; Konietschke, Frank; Rudolph, Volker; et al.
Abstract: Aims: Timely referrals for transplantation and left ventricular assist device (LVAD) play a key role in favourable outcomes in patients with advanced heart failure (HF). The purpose of the Catheter Ablation for atrial fibrillation in patientS with end‐sTage heart faiLure and Eligibility for Heart Transplantation (CASTLE‐HTx) trial is to test the hypothesis that atrial fibrillation (AF) ablation has beneficial effects on mortality and morbidity during 'waiting time' for heart transplantation (HTx) or to prolong the time span until LVAD implantation. Methods and Results: CASTLE‐HTx is a randomized evaluation of ablative treatment of AF in patients with severe left ventricular dysfunction who are candidates and eligible for HTx. The primary endpoint is the composite of all‐cause mortality, worsening of HF requiring a high urgent transplantation, or LVAD implantation. The secondary study endpoints are all‐cause mortality, cardiovascular mortality, cerebrovascular accidents, worsening of HF requiring unplanned hospitalization, AF burden reduction, unplanned hospitalization due to cardiovascular reason, all‐cause hospitalization, quality of life, number of delivered implantable cardioverter defibrillator therapies, time to first implantable cardioverter defibrillator therapy, number of device‐detected ventricular tachycardia/ventricular fibrillation episodes, left ventricular function, exercise tolerance, and percentage of right ventricular pacing. Ventricular myocardial tissue will be obtained from patients who will undergo LVAD implantation or HTx to assess the effect of catheter ablation on human HF myocardium. CASTLE‐HTx will randomize 194 patients over a minimum time period of 2 years. Conclusions: CASTLE‐HTx will determine if AF ablation has beneficial effects on mortality in patients with end‐stage HF who are eligible for HTx.